Анализа укорељености нивоа серумског ПАЦАП-38, Фибулин-3 и ТЕМ1 са срчаном функцијом и прогнозом код пацијената са хроничном срчаном инсуфицијенцијом: Нивои серума ПАКАП-38, Фибулин-3 и ТЕМ1 код хроничне срчане инсуфицијенције - Chen, Yan; Zeng, Fanlong; Gao, Tianyun; Hu, Bayi; Zhang, Mo; Yu, Zongliang (Journal of Medical Biochemistry, 2025)
Objective: To analyze the relationships between the levels of serum fibrinum-3 (Fibulin-3), antihuman tumor endothelial marker 1 (TEM1), and pituitary adenylate cyclase-activating polypeptide-38 (PACAP-38) in elderly chronic heart failure (CHF) patients and classification of cardiac function and a negative prognosis. Methods: A total of 132 elderly CHF patients who were admitted to the hospital between July 2022 and July 2024 were chosen as the elderly CHF group, and 132 healthy people who were examined in the hospital during that time were chosen as the control group. According to the cardiac function classification criteria of the New York Heart Association (NYHA), Grade II (42 patients), Grade III (51 patients), and Grade IV (39 patients) groups were created from the elderly CHF patients. Based on whether MACE happened after discharge, elderly CHF patients were split into two groups: those who experienced MACE and those who did not. The levels of serum Fibulin-3, TEM1 and PACAP-38 in all the subjects were detected via ELISA. Serum Fibulin-3, TEM1, and PACAP-38 levels were correlated with cardiac function categorization in older CHF patients using Spearman correlation analysis. Older patients with CHF had their MACEs examined using multivariate logistic regression analysis. Serum Fibulin-3, TEM1, and PACAP-38 were evaluated for their predictive value of MACEs in older individuals with CHF. Results: While the elderly CHF group’s serum levels of Fibulin-3 and PACAP-38 were lower than those of the control group, their serum levels of TEM1 were higher. P<0.05 indicated that the differences were statistically significant. Serum TEM1 levels are compared across various cardiac function categories in elderly CHF patients. Serum Fibulin-3 and PACAP-38 levels in older CHF patients with varying cardiac function grades were compared, and the results showed the following pattern: Grade II > Grade III > Grade IV. Spearman correlation analysis revealed that there was a favorable correlation between the serum TEM1 level and the heart function classification of elderly CHF patients (rs=0.488, P<0.05) and Fibulin-3 and PACAP-38 (rs=-0.463, -0.432, P<0.05). The MACE group had lower levels of serum Fibulin-3 and PACAP-38 than the non-MACE group, whereas the level of serum TEM1 and the proportion of patients with cardiac function grade IV were greater than those in the non-MACE group. Multivariate logistic regression analysis revealed that elevated levels of serum Fibulin-3 and PACAP-38 were protective factors against MACEs, whereas elevated levels of serum TEM1 and cardiac function grade IV were risk factors for MACEs. According to the ROC curve study, the areas under the curve (AUCs) of serum Fibulin-3, TEM1, and PACAP-38 alone and the combination of the three indicators for predicting MACEs in patients with CHF were 0.666, 0.636, 0.641, and 0.798, respectively. The AUC predicted by the combination of the three indicators was greater than that of serum Fibulin-3, TEM1, and PACA. The AUC predicted by P-38 alone (Z3 combined with Fibulin-3=2.448, P=0.014; Z3 combined with TEM1=2.033, P=0.042; Z3 combined with PACAP-38=2.200, P=0.028). Conclusion: Serum Fibulin-3 and PACAP-38 levels were considerably lower in older CHF patients, whereas the level of TEM1 was significantly increased. These three factors together demonstrated a comparatively high predictive value for MACE occurrence in older CHF patients.